Death In Venice And Other Stories - Thomas Mann & David Luke
Gustav von Aschenbach, a successful ageing writer, travels to Venice for a holiday. One day, at dinner in his hotel, Aschenbach notices an exceptionally beautiful young boy. Soon his days begin to revolve around seeing this boy and he is too distracted to pay attention to the ominous rumours that have begun to circulate about disease spreading through the city. Italian director Luchino Visconti also wrote the screenplay for his 1971 adaptation of Mann's novella and travelled all over the world in search of a suitable actor for the role of Tadzio. Dirk Bogarde considered retiring after playing the part of Aschenbach, believing he could never hope to give a better perfomance in a better film.